Macro-economic policy : a comparative study, Australia, Canada, New Zealand, South Africa - Perkins, J. O. N. (Toronto : Buffalo] : University of Toronto Press, 1973)
This book considers and compare some of the macro-economic problems and policies of this group of countries, Australia, Canada, South Africa and New Zealand.
Includes index
Includes bibliographies footnotes
usc 31/07/2017
Loans
Keywords: Economic policy; Australia; Canada; New Zealand; South Africa